2011
DOI: 10.1136/bmj.d5956
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and autoimmune disorders after vaccination against pandemic influenza A (H1N1) with a monovalent adjuvanted vaccine: population based cohort study in Stockholm, Sweden

Abstract: Objective To examine the risk of neurological and autoimmune disorders of special interest in people vaccinated against pandemic influenza A (H1N1) with Pandemrix (GlaxoSmithKline, Middlesex, UK) compared with unvaccinated people over 8-10 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 26 publications
5
109
5
1
Order By: Relevance
“…Similar results have been reported in a retrospective cohort study in active components of US Military between 2002-2008 [153]. Another retrospective cohort study in Sweden examining the risk of autoimmune and neurological disorders in people vaccinated against pandemic influenza A demonstrated no changes in the frequency of several autoimmune diseases, including T1DM [154].…”
Section: Vaccines and Risk Of T1dmsupporting
confidence: 73%
“…Similar results have been reported in a retrospective cohort study in active components of US Military between 2002-2008 [153]. Another retrospective cohort study in Sweden examining the risk of autoimmune and neurological disorders in people vaccinated against pandemic influenza A demonstrated no changes in the frequency of several autoimmune diseases, including T1DM [154].…”
Section: Vaccines and Risk Of T1dmsupporting
confidence: 73%
“…This risk is consistent with the level of risk reported by others. Estimates from single-country studies ranged from 1.05 to 4.70, the majority of which reported statistically significant increased risk [23][24][25][26][27][28][29][30][31][32]. Estimates were lower in studies of adjuvanted vaccines (1.05-3.04) [25,31] than in non-adjuvanted vaccines (1.57-4.70) [26][27][28][29][30]32].…”
Section: Discussionmentioning
confidence: 92%
“…The investigations revealed that some particles are embedded in a biological substrate, probably proteins, endo-toxins and residues of bacteria. As soon as a particle comes in contact with proteic fluids, a nano-bio-interaction [6] occurs and a "protein corona" is formed [7][8][9][10]. The nano-bio-interaction generates a biggersized compound that is not biodegradable and can induce adverse effects, since it is not recognized as self by the body.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the diphtheria-tetanus-pertussis (DTaP) vaccine was linked to cases of sudden infant death syndrome (SIDS) [3]; measles-mumps-rubella vaccine with autism [4,5]; multiple immunizations with immune disorders [6]; hepatitis B vaccines with multiple sclerosis, etc.…”
Section: Introductionmentioning
confidence: 99%